Store-Operated Ca2+ Entry Does Not Control Proliferation in Primary Cultures of Human Metastatic Renal Cellular Carcinoma. (9th July 2014) - Dragoni, Silvia; Turin, Ilaria; Laforenza, Umberto; Potenza, Duilio Michele; Bottino, Cinzia; Glasnov, Toma N.; Prestia, Martina; Ferulli, Federica; Saitta, Anna; Mosca, Alessandra; Guerra, Germano; Rosti, Vittorio; et al.
Abstract : Store-operated Ca 2+ entry (SOCE) is activated following depletion of the inositol-1, 4, 5-trisphosphate (InsP3 )-sensitive Ca 2+ pool to regulate proliferation in immortalized cell lines established from either primary or metastatic lesions. The molecular nature of SOCE may involve both Stim1, which senses Ca 2+ levels within the endoplasmic reticulum (ER) Ca 2+ reservoir, and a number of a Ca 2+ -permeable channels on the plasma membrane, including Orai1, Orai3, and members of the canonical transient receptor (TRPC1–7) family of ion channels. The present study was undertaken to assess whether SOCE is expressed and controls proliferation in primary cultures isolated from secondary lesions of heavily pretreated metastatic renal cell carcinoma (mRCC) patients. SOCE was induced following pharmacological depletion of the ER Ca 2+ store, but not by InsP3 -dependent Ca 2+ release. Metastatic RCC cells express Stim1-2, Orai1–3, and TRPC1–7 transcripts and proteins. In these cells, SOCE was insensitive to BTP-2, 10 µ M Gd 3+ and Pyr6, while it was inhibited by 100 µ M Gd 3+, 2-APB, and carboxyamidotriazole (CAI). Neither Gd 3+ nor 2-APB or CAI impaired mRCC cell proliferation. Consistently, no detectable Ca 2+ signal was elicited by growth factor stimulation. Therefore, a functional SOCE is expressed but does not control proliferation of mRCC cells isolated from patients resistant to multikinase inhibitors.